Pattern of Refractive Error in Primary School Children in Rupandehi District, Nepal - Rai, Salma K.C.; Thapa, Hari Bahadur; Gurung, Nanda; Bhari, Arjun Malla; Sharma, Manoj K (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Refractive error remains one of the primary causes of visual impairment in children worldwide. This study describes pattern of refractive errors among primary school students in Rupandehi district, Nepal. MATERIAL AND METHODS: Records of 128 children with refractive error aged 5-15 years from both urban and rural areas in Nepal between January and March 2011 were examined for patterns in the distribution of refractive errors. SPSS statistical software was used to perform analysis. RESULTS: The commonest type of refractive errors among the children was astigmatism (47%) followed by myopia (26%) and hyperopia (19%). Children in the age group 11-15 years had higher number of eyes with refractive error as compared to their younger counterparts 5 years /or below 5 years (49% vs. 9%). 71% students were from schools located in rural areas. Among the children with refractive errors, only 44.5% students were wearing glasses. 57% of the students studying in private schools were wearing glasses but only 26.9% students from the government school were wearing glasses. CONCLUSION: A wide variation in the distribution of refractive errors between the geographic locations, gender basis, types of schools as well as between the different ethnic groups was observed. Journal of Universal College of Medical Sciences Vol. 3, No. 1, 2015: 31-36